Differences in white matter connectivity between treatment-resistant and treatment-responsive subtypes of schizophrenia. (30th December 2018) - McNabb, Carolyn Beth; Kydd, Rob; Sundram, Frederick; Soosay, Ian; Russell, Bruce Roy
Highlights: DWI shows differences between first-line responders and those in need of clozapine. There was no difference between groups in the mean AD of the corpus callosum. Lower FA and greater RD in the CC could be a marker of treatment resistance. Abstract: Schizophrenia is a heterogeneous disorder exhibiting variable responsiveness to treatment between individuals. Previous work demonstrated that white matter abnormalities may relate to antipsychotic response but no study to date has examined differences between first-line treatment responders (FLR) and clozapine-eligible individuals receiving first-line antipsychotics. The current study aimed to establish whether differences in white matter structure exist between these two cohorts. Diffusion-weighted images were acquired for 15 clozapine-eligible and 10 FLR participants. Measures of fractional anisotropy (FA), radial diffusivity (RD) and axial diffusivity (AD) were obtained and between-group t -tests interrogating differences in FA were conducted. To investigate the neural basis of a decrease in FA, the significant cluster from FA analysis was masked and used to obtain mean RD and AD measures for that region. Those who were clozapine-eligible had significantly lower FA in the body of the corpus callosum ( p < 0.05), associated with a significant increase in mean RD compared with FLR ( p < 0.001). No difference in mean AD was observed for this region. These data reveal differences in diffusion measures between FLR and those eligible for clozapine and suggest that lower FA and greater RD in the corpus callosum could exist as a biomarker of treatment resistance in people with schizophrenia.